SYNTHESIS AND ANTIMICROBIAL ACTIVITY EVALUATION OF ETHYL SALICYL FUMARATE AND ETHYL FURFURYL FUMARATE - Jumina .; Iqbal Tahir; Abdul Karim Zulkarnain (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
This research was conducted in order to synthesize and investigate the antimicrobial activity of ethyl salicyl fumarate and ethyl furfuryl fumarate. These two target molecules were chosen as the former is the derivative of C-9154 antibiotic containing phenolic hydroxyl group, whereas the latter is an example of C-9154 antibiotic derivative bearing furan ring instead of benzene.Ethyl salicyl fumarate was synthesized from methyl salicylate through reduction with LiAlH4, condensation of salicyl alcohol with maleic anhydride, and esterification of salicyl maleic acid with ethanol in the presence of benzenesulfonic acid as the catalyst. These reactions gave satisfactory yields (76-92 %) in all steps involved. Similar to this procedure, ethyl furfuryl fumarate was prepared from furfural through reduction with NaBH4 followed by condensation of the resulted furfuryl alcohol with maleic anhydride and esterification of furfuryl maleic acid with ethanol in the presence of benzenesulfonic acid. Although the reduction of furfural and the condensation of furfuryl alcohol with maleic anhydride could be performed smoothly, the esterification of furfuryl maleic acid with ethanol only gave 38 % yield of ethyl furfuryl fumarate.The results of antimicrobial activity test showed that the value of minimum inhibition concentration (MIC) of salicyl maleic acid and ethyl salicyl fumarate towards Staphyllococcus aureus were 500 and 100 μg/mL, whereas towards Eschericia coli were 2000 and 4000 μg/mL respectively. In contrast, the MIC values of furfuryl maleic acid and ethyl furfuryl fumarate towards Staphyllococcus aureus and Eschericia coli were 150 and 100 μg/mL respectively.Keywords: synthesis, activity, C-9154 antibiotic, fumarate